A photosynthetic bacterial inoculant exerts beneficial effects on the yield and quality of tomato and affects bacterial community structure in an organic field - Lee, Sook-Kuan; Chiang, Ming-Shu; Hseu, Zeng-Yei; Kuo, Chih-Horng; Liu, Chi-Te (Frontiers in Microbiology, 2022)
Plant growth-promoting rhizobacteria (PGPRs) are microorganisms that promote plant health and play critical roles in sustainable agriculture. As a PGPR, Rhodopseudomonas palustris strain PS3, when applied as a microbial inoculant, exhibited beneficial effects on a variety of crops. In this study, we investigated the effects of PS3 on tomato growth, soil properties, and soil microbiota composition in an organic field. The results demonstrated that PS3 inoculation significantly improved fruit yield and quality. Additionally, soil nutrient availability and enzymatic activities were increased. Furthermore, several bacterial genera known to be associated with nutrient cycling (e.g., Dyella, Novosphingobium, Luteimonas, Haliangium, and Thermomonas) had higher relative abundances in the PS3-treated soil. To validate the results of the field experiment, we further conducted pot experiments with field-collected soil using two different tomato cultivars and obtained consistent results. Notably, the relative abundance of putative PGPRs in the genus Haliangium was significantly higher with PS3 inoculation in both cultivars, suggesting that this genus may have synergistic interactions with PS3. Taken together, we further demonstrated the value of PS3 in sustainable agriculture and provided novel knowledge regarding the effects of this PGPR on soil microbiota composition.